Surgical and prosthodontics management of a perforating giant radicular cyst in anterior maxilla: a case report - Motiwala, Momina Anis; Zafar, Kamil; Farhan Raza Khan (Journal of the Pakistan Medical Association, 2022)
Abstract Radicular cyst is the most common type of odontogenic cyst associated with the apex of non-vital teeth. The lining of the radicular cyst usually arises from the epithelial rests of Malassez. These cyst usually persists even after the elimination of microbial load from the root canals. Surgical removal is deemed necessary for the management. For larger lesions extending to the facial or palatal cortical plates, additional regenerative procedures such as bone grafting along with collagen membrane are warranted. This case report describes the surgical and prosthetic management of a giant radicular cyst that was perforating the cortical plates in the anterior maxilla. Key words: cysts, radicular cyst; bone grafting, esthetic management, regeneration.